2018
DOI: 10.1177/0143034318803666
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ perceptions of school climate: Exploring its protective role in times of economic recession

Abstract: The aim of the study is to explore the way Greek junior high school students perceive school climate as a protective factor against the adversities due to the ongoing economic recession. The randomly selected sample consisted of 746 students from junior high schools (Gymnasia) in the broader area of Athens. The California School Climate Survey (2009), the Questionnaire of Subjective Well-Being/Youth Form (Grob et al., 1991) and the Economic Crisis Difficulties Questionnaire (LSP, 2011) were used for data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Wagle et al (2018) employed structural equation modeling techniques and focused on validating a measure of student belonging (used interchangeably with connectedness or engagement) among primary school students in three countries including the United States, China, and the United Kingdom. Hatzichristou, Stasinou, Lampropoulou, & Lianos (2018) extended the examination of school climate and found important findings regarding the influence of positive peer relations and social and emotional support on the emotional effects of an economic recession on subjective well-being among middle school students from Greece. Confirmatory factor analyses were conducted to confirm the factor structure of the surveys used within the study.…”
Section: Overview Of the Present Contributionsmentioning
confidence: 89%
See 2 more Smart Citations
“…Wagle et al (2018) employed structural equation modeling techniques and focused on validating a measure of student belonging (used interchangeably with connectedness or engagement) among primary school students in three countries including the United States, China, and the United Kingdom. Hatzichristou, Stasinou, Lampropoulou, & Lianos (2018) extended the examination of school climate and found important findings regarding the influence of positive peer relations and social and emotional support on the emotional effects of an economic recession on subjective well-being among middle school students from Greece. Confirmatory factor analyses were conducted to confirm the factor structure of the surveys used within the study.…”
Section: Overview Of the Present Contributionsmentioning
confidence: 89%
“…The sample included junior high school students in Greece. Hatzichristou et al (2018) explain that subjective well-being describes the degree to which an individual feels satisfied with their life, and the evaluation is derived from their personal criteria. The authors report that impact of an economic recession can have an adverse effect on adolescents' subjective well-being; they often feel less satisfied with themselves and more worried about themselves and others (Ro¨zer & Kraaykamp, 2013;Sacks, Stevenson, & Wolfers, 2010).…”
Section: Overview Of the Present Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies discovered common domains of school climate and also took into consideration the complexity of these domains (Ramelow, Currie, & Felder-Puig, 2015). In some studies that were cited by Hatzichristou et al (2018), there are significant dimensions of a positive school climate all similarly includes (Cohen et al, 2009;Zullig, Koopman, Patton, & Ubbes 2010): (a) safety in school help in promoting the academic status and resilience of the student (Gietz & McIntosh, 2014); (b) interpersonal relationships that comprises of shared understandings, positive relationships with peers and teachers, all contributing to better academic and psychological adjustment of transfer students (Doll, Brehm, & Zucker, 2014); (c) perceptions of the student towards the learning process, the engagement, and satisfaction of the student (Finnan, Schnepel, & Anderson, 2003); (d) Dimensions of school engagement, behavioral, emotional, and cognitive, all being used in the learning process (Lam et al, 2016); (e) the school's physical environment related to better academic performance and sense of belongingness (McNeely, Nonnemaker & Blum, 2002). Overall, the adaptation to the school climate with the help of peer relations and support of the school environment is an essential factor for a successful transition of transfer students (Lester & Cross, 2015).…”
Section: Resiliencementioning
confidence: 99%
“…This situation has had an intense impact on school communities, thus creating a great need for intervention programs to support schools, communities, and underprivileged members of society (Hatzichristou, Stasinou, Lampropoulou, & Lianos, 2018). Studies conducted in Greece have revealed various problems related to the economic recession in school infrastructure; for example, teachers both in primary and secondary schools have reported increased interpersonal and intrapersonal behavioral difficulties (in addition to other changes) among students due to reductions in families’ incomes (Anagnostopoulos & Soumaki, 2012; Hatzichristou, 2017).…”
mentioning
confidence: 99%